New C-14 Datings of Late Palaeolithic Cultures from Northwestern Europe - Fischer, Anders; Tauber, Henrik (Journal of Danish Archaeology, 1986)
New C-14 Datings of Late Palaeolithic Cultures from Northwestern Europe